Acute stress in adulthood impoverishes social choices and triggers aggressiveness in preclinical models - Nosjean, Anne; Cressant, Arnaud; de Chaumont, Fabrice; Olivo-Marin, Jean-Christophe; Chauveau, Fredéric; Granon, Sylvie (Frontiers in Behavioral Neuroscience, 2015)
Adult C57BL/6J mice are known to exhibit high level of social flexibility while mice lacking the β2 subunit of nicotinic receptors (β2-/- mice) present social rigidity. We asked ourselves what would be the consequences of a restraint acute stress (45 min) on social interactions in adult mice of both genotypes, hence the contribution of neuronal nicotinic receptors in this process. We therefore dissected social interaction complexity of stressed and not stressed dyads of mice in a social interaction task. We also measured plasma corticosterone levels in our experimental conditions. We showed that a single stress exposure occurring in adulthood reduced and disorganized social interaction complexity in both C57BL/6J and β2-/- mice. These stress-induced maladaptive social interactions involved alteration of distinct social categories and strategies in both genotypes, suggesting a dissociable impact of stress depending on the functioning of the cholinergic nicotinic system. In both genotypes, social behaviors under stress were coupled to aggressive reactions with no plasma corticosterone changes. Thus, aggressiveness appeared a general response independent of nicotinic function. We demonstrate here that a single stress exposure occurring in adulthood is sufficient to impoverish social interactions: stress impaired social flexibility in C57BL/6J mice whereas it reinforced β2-/- mice behavioral rigidity.